2017
DOI: 10.22159/ijpps.2017v9i7.15387
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Olive Leaf Extract Ointment on Pain Intensity and Early Maternal Complications in Primiparous Women

Abstract: Objective: This study aimed to assess the impact of olive leaf extract ointment on pain intensity and early maternal complications in primiparous women. Methods:This randomized clinical trial was conducted on 90 primiparous women. The participants were randomly divided into three groups each containing 30 women. Groups A, B, and C used olive leaf extract ointment, placebo ointment, and betadine solution at the episiotomy area three times a day for 10 d. Improvement of the episiotomy wound was evaluated using R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 13 publications
0
12
1
Order By: Relevance
“…The results obtained showed 56% incidence of striae in the control group and 36% in the intervention [27]. In their study, Osman et al reported incidence of striae 48.8% of cocoa cream users and 45.1% in the control group [28,29]. The results of these studies disagree with the present study results, probably due to the difference in study objectives, which were treatment in the present study, and prevention in most of the above studies.…”
Section: Discussioncontrasting
confidence: 87%
“…The results obtained showed 56% incidence of striae in the control group and 36% in the intervention [27]. In their study, Osman et al reported incidence of striae 48.8% of cocoa cream users and 45.1% in the control group [28,29]. The results of these studies disagree with the present study results, probably due to the difference in study objectives, which were treatment in the present study, and prevention in most of the above studies.…”
Section: Discussioncontrasting
confidence: 87%
“…However, in the study by Tsay et al (2008) to determine the effectiveness of feet reflexotherapy in mitigating pain and anxiety in patients after stomach cancer surgery and blood cell cancer in Taiwan, the treatment group (massaging the digestive reflex points, i.e., upper and lower parts of the abdomen, liver, spleen, gallbladder, duodenum) had consumed significantly less painkiller. It seems that difference in massage points is the reason of different results between the two studies [28,31].…”
Section: Jahani Et Almentioning
confidence: 96%
“…[ 13 ] According to a study, Iranian midwives use episiotomy incision most frequently (88%). [ 7 ] Therefore, considering to importance of avoiding unnecessary interventions and reducing the pain and suffering of mothers during and after delivery, changing the attitude of staff in delivery units toward minimizing use of episiotomy is essential. Until then, changing attitudes lead to performance modification.…”
Section: Introductionmentioning
confidence: 99%